BIOLOGICAL AND ECONOMIC IMPORTANCE OF FOREST GYMNOSPERMS - Djabborov Bakhtiyor Iskandarovich; Shamsieva Nilufar; Bobokulova Nozima (Journals Park Publishing, 2023)
The article presents data on the biological and economic features of forest gymnosperms, their chemical composition, medicinal properties, and use in the national economy.
Keywords: viscose, silk, cellulose, staple, balm, resin, pine wool, camphor, alcohol, acetic acid, tannic extracts, turpentine, rosin, tar, charcoal, pine essential oil, taiga, Pinus roxburghii, P. wallichiana, P. merkusii and P. insularis.